Cyberfraud - Graham, Roderick (Cybercrime and digital deviance, 2024)
In this chapter, the reader is introduced to cyberfraud. Noting the ubiquitousness of digitized personal information and data transactions taking place via digital means, the chapter covers a broad range of concepts and practices concerning deception and theft in the digital world. Included in the chapter are discussions of romance scams, advance fee frauds, identity theft, digital piracy, and an array of fraudulent communications labeled based upon the technology used to facilitate the attacks (i.e., phishing, vishing, smishing, and pharming). This chapter also presents the reader with frauds facilitated by emerging financial technologies like NFTs and cryptocurrency.